Global crises and equity market contagion - Geert Bekaert; Michael Ehrmann; Marcel Fratzscher; Arnaud Mehl (European Central Bank (ECB), 2011)
Using the 2007-2009 financial crisis as a laboratory, we analyze the transmission of crises to country-industry equity portfolios in 55 countries. We use an asset pricing framework with global and local factors to predict crisis returns, defining unexplained increases in factor loadings as indicative of contagion. We find evidence of systematic contagion from US markets and from the global financial sector, but the effects are very small. By contrast, there has been systematic and substantial contagion from domestic equity markets to individual domestic equity portfolios, with its severity inversely related to the quality of countries' economic fundamentals and policies. Consequently, we reject the globalization hypothesis that links the transmission of the crisis to the extent of global exposure. Instead, we confirm the old “wake-up call” hypothesis, with markets and investors focusing substantially more on idiosyncratic, country-specific characteristics during the crisis.
Keywords: F3; G14; G15; 330; Contagion; country risk; current account; equity markets; factor model; financial crisis; financial policies; FX reserves; global transmission; market integration